STRATEGI PENGAJARAN BAHASA ARAB DENGAN PENDEKATAN KONTEKSTUAL DI KELAS 2 STTD AL BIRRU MAJENANG - Alif Fia Damayanti; Anisa Rahayu Ardani; Mauhibah Nur Imtiyas; Amrin Mushtofa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The strategy of teaching arabic with a contextual approach is a learning method that connects the arabic with the daily life context of the students, making the learning process more meaningful and enjoyable. This study aims to analyze the application of the teaching strategy of arabic using a contextual approach in the second grade at STTD Al Birru Majenang. The method used is qualitative, employing observation, interviews, and documentation for data collection. The results show that the use of a contextual approach in teaching arabic can improve students' interest and skills in the language. Students become more active participants because the material taught is directly related to their experiences and surroundings. This approach also helps students understand the vocabulary and sentences of arabic that are relevant to daily life, facilitating easier memorization and practical use of the language. The learning activities, which are active, creative, and collaborative, create an enjoyable and engaging learning atmosphere. In conclusion, the teaching strategy of arabic with a contextual approach is effective to increase motivation and competence in arabic for second-grade students at STTD Al Birru Majenang.